Development of a flipbook-based e-module on the human circulatory system - Serina, Serina; Panjaitan, Ruqiah Ganda Putri; Wahyuni, Eko Sri (Biosfer: Jurnal Pendidikan Biologi, 2025)
Teaching materials for the human circulatory system are still limited to printed books, which lack interactivity and do not provide visual representations for understanding its anatomical structure. The development of interactive e-modules is needed to facilitate more effective learning through the integration of text, images, videos, and interactive elements. This research seeks to determine both the viability and student response to an interactive heyzine-based electronic module covering the human circulatory system submaterial, exploring its potential as a more engaging alternative educational resource. The study employed a modified Research and Development methodology based on the Borg and Gall model as adapted by Sugiyono. Researcher selected participants through purposive sampling, involving 36 eighth-grade junior high school students. The research utilized validation sheets and student response questionnaires. The research instruments were validated by 5 expert validators. The researcher used content validity analysis methods, specifically Aiken's V coefficient, to analyze the collected data. Reliability testing using Intraclass Correlation Coefficients. Assessment of student response questionnaire using the Likert scale. The teaching material validation analysis produced an average score of 0.92, placing it in the valid category. Reliability testing yielded a score of 0.806, which falls within the good classification. Students responded favorably to the developed educational materials, with an average positive response rate of 77.57%, indicating good reception. Based on these findings, we determined that the developed heyzine-based electronic module covering the human circulatory system sub-material is appropriate for educational implementation.